Fitting the name or unworthy of the name?—Does the name of family firm major shareholder influence family’s egoistic behavior? - Yu, Xiaodong; Li, Huan; Cheng, Xirong; Sun, Shize (Frontiers in Psychology, 2022)
It has been generally believed that the major shareholders of family firms are more willing to implement egoistic behaviors aimed at benefiting the family. This study analyses whether the major shareholder of the family firm whose name contains “Confucian symbols” such as benevolence, righteousness, loyalty, and kindness will reduce family self-interested behaviors as his name indicates. Using a sample consisting of all 425 family firms listed on Small and Medium Enterprise Board and Growth Enterprise Board, the result shows that the major shareholder whose name contains Confucian symbols is less likely to misappropriate corporate assets and less likely to make “family-first” personnel arrangements, meanwhile is more open to external supervision. Further mechanism testing reveals that the major shareholder whose name contains Confucian symbols also tends to choose corporate culture that reflects Confucianism. The study confirms that the name of the major shareholder is one of the factors which can affect the operation of the family business, demonstrates that different family firms have different attitudes towards family self-interest, and promotes the extant research from the “differences between family and non-family firms” level further to the “differences among family firms running by different families” level.